2017
DOI: 10.1038/srep44041
|View full text |Cite
|
Sign up to set email alerts
|

The redox environment triggers conformational changes and aggregation of hIAPP in Type II Diabetes

Abstract: Type II diabetes (T2D) is characterized by diminished insulin production and resistance of cells to insulin. Among others, endoplasmic reticulum (ER) stress is a principal factor contributing to T2D and induces a shift towards a more reducing cellular environment. At the same time, peripheral insulin resistance triggers the over-production of regulatory hormones such as insulin and human islet amyloid polypeptide (hIAPP). We show that the differential aggregation of reduced and oxidized hIAPP assists to mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 55 publications
(64 reference statements)
10
87
0
Order By: Relevance
“…Recently, a novel ssNMR-based structure of the FUS amyloid core was reported, with similar structural features as noted above for other amyloid structures[101]. The peptide IAPP (also known as amylin) forms amyloid-like fibrils in type II diabetes, which have also been studied recently by ssNMR [102]. Human β-2-microglobulin (β2m) is involved in dialysis-related amyloidosis.…”
Section: Protein Aggregation In Human Diseasementioning
confidence: 78%
“…Recently, a novel ssNMR-based structure of the FUS amyloid core was reported, with similar structural features as noted above for other amyloid structures[101]. The peptide IAPP (also known as amylin) forms amyloid-like fibrils in type II diabetes, which have also been studied recently by ssNMR [102]. Human β-2-microglobulin (β2m) is involved in dialysis-related amyloidosis.…”
Section: Protein Aggregation In Human Diseasementioning
confidence: 78%
“…By reducing IAPP aggregation with detergent micelles, solution NMR studies have been used to study the structure of IAPP monomers. 137139 It has been shown that SDS micelles stabilize IAPP in a highly helical form (Fig. 7b–d).…”
Section: Iapp and Type 2 Diabetesmentioning
confidence: 96%
“…α -Helical intermediates have been detected during the lag phase for amyloid formation in amyloid- β , α -synuclein, and human islet amyloid polypeptide (hIAPP, also known as amylin), by CD, 2729 NMR 29,30 EPR, 31 and fluorescence and neutron reflectometry 32 studies. There is evidence for antiparallel β -sheet structure in intermediates of amyloid- β , 33 α -synuclein, 34 and the SH3 domain.…”
Section: Introductionmentioning
confidence: 99%